Training Needs Assessment: Basis For Institutional Personnel Development Plan - Roldan, Amalia (International Journal of Educational Research & Social Sciences, 2022)
This study was conducted to determine the training needs of the OMSC administrators, teaching and non-teaching personnel. A total of 125 administrators (10), teaching (90) and non-teaching personnel (25) were identified as the subjects of this study. Existing records were used to determine the number of trainings attended by the in 2019. To identify the competency gaps of the personnel, an evaluation was conducted using the competency standards evaluation instruments for teaching, non-teaching and administrators validated by the researcher. Descriptive type of research was employed in this study since it focuses on needed training of the personnel for the enhancement of the job performance, weighted mean was used to analyze the result of the seminars and trainings attended, competency gaps and job performance. Findings of the study showed (1) majority of the seminars, training and conferences attended by the administrators and non-teaching personnel are in the national level about leadership and governance while for the teaching personnel are at the local level in the area of instruction. (2) The OMSC administrators have high level of competency on managerial/supervisory skills in terms of decision making, work standards and optimal performance. The competency gap is on planning and organizing and managing conflicts. The teaching personnel have high level of competency in terms of the mastery of the subject matter and classroom management. The competency gap is reflected on the teaching skills, teacherstudent relationship and assessment and evaluation. The non-teaching personnel showed high level of competency on cooperation, initiative and ability to learn. On the other hand, the personnel need interventions in terms of their respective job knowledge and organizational ability. (3) The OMSC personnel showed high level of job performance.